Neuroscience in medicine edited by P. Michael Conn. - Conn, P. Michael (Humana Press, 2003)
Enormous progress has been made in understanding the brain at the molecular, anatomic, and physiological levels in the years following the "Decade of the Brain," with the results providing insight into the underlying basis of many neurological disease processes. In Neuroscience in Medicine, Second Edition, P. Michael Conn and a distinguished panel of basic and clinical investigators noted for their teaching excellence have thoroughly updated and revised their classic first edition to reflect these remarkable advances. Designed specifically for medical students and allied health professionals, the book alternates scientific and clinical chapters that explain the basic science underlying neurological processes and then relate that science to the understanding of neurological disorders and their treatment. These popular "clinical correlations" cover, in detail, disorders of the spinal cord, neuronal migration, the autonomic nervous system, ocular motility, and the basal ganglia, as well as demyelinating disorders, stroke, dementia and abnormalities of cognition, Parkinson's disease, nerve trauma, peripheral neuropathy, aphasias, and myasthenia gravis. Materials new to this revised edition include full chapters on the thalamus, pain, immune system interactions with the nervous system, and the anatomy of the spinal cord and brain. In addition to concise summaries of the most recent biochemical, physiological, anatomical, and behavioral advances, the book summarizes up-to-date findings on neuronal gene expression and protein synthesis at the molecular level. Authoritative and comprehensive, Neuroscience in Medicine, Second Edition provides a fully up-to-date and readily accessible guide to brain functions at the cellular and molecular level, as well as clearly demonstrating their emerging diagnostic and therapeutic importance.